HUBUNGAN PENGETAHUAN MASYARAKAT TENTANG PENYAKIT MALARIA DENGAN PERILAKU PENCEGAHAN DI WILAYAH KERJA PUSKESMASMEDICAL CENTRE LIMBOTO BARAT KECAMATAN LIMBOTO BARAT - Rona Febriyona; Rini Asnawati (-, 2021)
This type of research is descriptive analytic with cross sectional approach, this population research is public of each village where the people never indicated exposed to malaria. to access the services at the social healthy center Medical Centre  west Limboto, with a sample of 43 people, sampling technique Total Sampling is done. Independent variables include public knowledge about malaria. Behavioral Prevention dependent variable. Data was collected using questionnaires and data from relevant agencies. Management of data using SPSS for windows version 16.0 statistical test Chi Square and presented in tabular and narrative. The results showed that p-value = 0.000 value smaller than the value of α = 0.05 (p <0.05), so it can be concluded that there is a relationship of knowledge with malaria prevention behaviors.